2018
DOI: 10.1016/j.nbd.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

The glycoprotein GPNMB is selectively elevated in the substantia nigra of Parkinson's disease patients and increases after lysosomal stress

Abstract: GPNMB is a glycoprotein observed upon tissue damage and inflammation and is associated with astrocytes, microglia, and macrophages. Gene variations in GPNMB are linked with Parkinson's disease (PD) risk, and changes in protein levels of GPNMB have been found in lysosomal storage disorders, including Gaucher's disease with glucocerebrosidase (GCase) deficiency. In the current study, GPNMB increases were seen in the substantia nigra (SN) of PD patients compared to age-matched controls. Such PD patients have a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
111
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 71 publications
3
111
0
1
Order By: Relevance
“…It is highly relevant to note that GPNMB has a neuroprotective role for TDP43 toxicity or ALS [127, 199]. GPNMB was also described as neurodegeneration biomarker in Alzheimer’s, Parkinson’s, Gaucher’s disease and PLOSL leukodystrophy [79, 82, 124, 126, 173].…”
Section: Resultsmentioning
confidence: 99%
“…It is highly relevant to note that GPNMB has a neuroprotective role for TDP43 toxicity or ALS [127, 199]. GPNMB was also described as neurodegeneration biomarker in Alzheimer’s, Parkinson’s, Gaucher’s disease and PLOSL leukodystrophy [79, 82, 124, 126, 173].…”
Section: Resultsmentioning
confidence: 99%
“…In cerebral spine fluid and brain of type 3 GD patients elevated gpNMB levels have also been observed [142]. Likewise, recently an increased level of gpNMB in the substantia nigra of PD patients was reported [143]. In mice with conditional deficiency in GCase in the white blood cell lineage Gaucher-like cells are formed.…”
Section: Lysosomal Glccer Deposits In Macrophages: Gaucher Cellsmentioning
confidence: 93%
“…These do not produce chitotriosidase or CCL18, but gpNMB does [140,144]. Inactivation of GCase with an irreversible inhibitor was found to increase gpNMB in the brain [143]. Interestingly, zebrafish and fruit flies overproduce a chitinase during GCase deficiency [130,145].…”
Section: Lysosomal Glccer Deposits In Macrophages: Gaucher Cellsmentioning
confidence: 99%
“…More related clinical studies with larger sample sizes are urgently needed. In despite of contradictory clinical results, researchers found that GPNMB was both transcriptionally and expressively elevated in the substantia nigra areas of PD patients (Murthy et al, 2017 ; Moloney et al, 2018 ; Neal et al, 2018 ). GPNMB could involve in regulation of inflammation and immune systems (Budge et al, 2018 ), which also participated in PD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%